2013
DOI: 10.1038/aja.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis to predict letrozole efficacy in improving sperm count of non-obstructive azoospermic and cryptozoospermic patients: a pilot study

Abstract: We tested the hypothesis that letrozole increases sperm count in non-obstructive azoospermic or cryptozoospermic patients with a testosterone (T)/17-beta-2-oestradiol (E2) ratio ,10. Forty-six patients with no chromosomal aberrations were randomized into two groups: 22 received letrozole 2.5 mg per day for 6 months (Group 1: 6 azoospermic116 cryptozoospermic patients), while 24 received a placebo (Group 2: 5 azoospermic119 cryptozoospermic patients). The following data were collected: two semen analyses, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
4
46
1
Order By: Relevance
“…Patients were not admitted to the study if any of the following criteria were present: refusal to participate in the study (5 patients); seminal white blood cell concentration >10 6 /mL or a positive seminal cultural analysis or positive urethral swab chlamydia test (6 patients); drug, tobacco, or alcohol abuse (8 patients); ongoing medical treatment (gonadotropins, anabolic steroids, cancer chemotherapy, non-steroidal anti-inflammatory drugs) (3 patients); dropout during the course of the study (3 patients); previous cancer radiotherapy or chemotherapy (2 patients); palpable varicocoele (10 patients); X-ray exposure in the previous 8 months (3 patients); Y chromosome microdeletion (1 patient); and karyotype alterations (0 patients); T/E2 < 10 (4 patients) (Koscinski et al, 2007;Cavallini et al, 2013). Patients were not admitted to the study if any of the following criteria were present: refusal to participate in the study (5 patients); seminal white blood cell concentration >10 6 /mL or a positive seminal cultural analysis or positive urethral swab chlamydia test (6 patients); drug, tobacco, or alcohol abuse (8 patients); ongoing medical treatment (gonadotropins, anabolic steroids, cancer chemotherapy, non-steroidal anti-inflammatory drugs) (3 patients); dropout during the course of the study (3 patients); previous cancer radiotherapy or chemotherapy (2 patients); palpable varicocoele (10 patients); X-ray exposure in the previous 8 months (3 patients); Y chromosome microdeletion (1 patient); and karyotype alterations (0 patients); T/E2 < 10 (4 patients) (Koscinski et al, 2007;Cavallini et al, 2013).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were not admitted to the study if any of the following criteria were present: refusal to participate in the study (5 patients); seminal white blood cell concentration >10 6 /mL or a positive seminal cultural analysis or positive urethral swab chlamydia test (6 patients); drug, tobacco, or alcohol abuse (8 patients); ongoing medical treatment (gonadotropins, anabolic steroids, cancer chemotherapy, non-steroidal anti-inflammatory drugs) (3 patients); dropout during the course of the study (3 patients); previous cancer radiotherapy or chemotherapy (2 patients); palpable varicocoele (10 patients); X-ray exposure in the previous 8 months (3 patients); Y chromosome microdeletion (1 patient); and karyotype alterations (0 patients); T/E2 < 10 (4 patients) (Koscinski et al, 2007;Cavallini et al, 2013). Patients were not admitted to the study if any of the following criteria were present: refusal to participate in the study (5 patients); seminal white blood cell concentration >10 6 /mL or a positive seminal cultural analysis or positive urethral swab chlamydia test (6 patients); drug, tobacco, or alcohol abuse (8 patients); ongoing medical treatment (gonadotropins, anabolic steroids, cancer chemotherapy, non-steroidal anti-inflammatory drugs) (3 patients); dropout during the course of the study (3 patients); previous cancer radiotherapy or chemotherapy (2 patients); palpable varicocoele (10 patients); X-ray exposure in the previous 8 months (3 patients); Y chromosome microdeletion (1 patient); and karyotype alterations (0 patients); T/E2 < 10 (4 patients) (Koscinski et al, 2007;Cavallini et al, 2013).…”
Section: Patientsmentioning
confidence: 99%
“…Eligible patients were those with normal semen appearance, consistency, liquefaction, volume, and pH. Patients were not admitted to the study if any of the following criteria were present: refusal to participate in the study (5 patients); seminal white blood cell concentration >10 6 /mL or a positive seminal cultural analysis or positive urethral swab chlamydia test (6 patients); drug, tobacco, or alcohol abuse (8 patients); ongoing medical treatment (gonadotropins, anabolic steroids, cancer chemotherapy, non-steroidal anti-inflammatory drugs) (3 patients); dropout during the course of the study (3 patients); previous cancer radiotherapy or chemotherapy (2 patients); palpable varicocoele (10 patients); X-ray exposure in the previous 8 months (3 patients); Y chromosome microdeletion (1 patient); and karyotype alterations (0 patients); T/E2 < 10 (4 patients) (Koscinski et al, 2007;Cavallini et al, 2013).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosschecking of the references and manual searches did not yield any additional studies for inclusion. Of these, three (Clark & Sherins, 1989;Gregoriou et al, 2012;Cavallini et al, 2013) studies met the inclusion criteria. Therefore, 42 further references were excluded from this review, as they were either case series or cross-sectional studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Another class of medication that has been used t o o p t i m i z e h o r m o n a l p a r a m e t e r s i n N O A a n d cryptozoospermia patients is aromatase inhibitors, such as anastrozole and letrozole. Although most studies were performed using anastrozole, which appears to have fewer side effects, one study comparing letrozole to placebo in cryptozoospermia and NOA patients suggested that letrozole may help enhance spermatogenesis with sperm return to the ejaculate in some NOA patients (24). Candidates for management with aromatase inhibitor include men with low serum testosterone (<300 ng/dL) and low testosterone: estradiol ratios (<10), in whom aromatase therapy has been suggested to enhance intratesticular testosterone levels and improve spermatogenesis (1,3,4).…”
Section: Medical Managementmentioning
confidence: 99%